KEBUGARAN KARDIORESPIRASI DAN INDEK MASA TUBUH MAHASISWA KKN-PPL PGSD PENJAS FIK UNY KAMPUS WATES TAHUN 2012 - Fredericus Suharjana (Jurnal Pendidikan Jasmani Indonesia, 2013)
Students attending KKN-PPL required to possess cardiorespiration fitness as well as good index of body mass andto know them need to test. This research carried out to know the fitness level of cardiorespiration and good indexof body mass for education and sport PGSD students in Wates Campus who attended KKN-PPL year 2012. Thisresearch method is survey with the subject of it is education and sport with study program PGSD students in WatesCampus who attended KKN-PPL year 2012, total numbers are 56 students consisting of 52 male and 4 femaleones. The technique of data withdrawal uses test and measurement. Instrumen for cardiorespiration fitness uses2,4 km running test from Cooper, and instrument for index of body mass measured by using IMB rule that is= BodyWeight (kg)/Body Height square (m). Result of the research shows that for cardiorespirasi fitness category: verygood and well trained is 1.8%; very good is 8.9%; good is 21.4%; medium is 37.5%; lack is 19.7%; and too lack is10.7%. While the result for mass body index category: fat is 5.4%; normal is 82.1%; and lack of nutrient I is 12.5%. Ifobserved based on type of sex, for male cardiorespiration fitness category: very good and well trained is 1.9%; verygood is 9.6%; good is 23.1%; medium is 38.5%; lack is 19.2%; and too lack is 7.7%. Female cardiorespiration fitnesscategory: medium is 25%; lack is 25%; and to lack is 50%. Index of body mass for male category: fat is 5.8%; normalis 80.8%; and lack of nutrient I is 13.4%. Whereas index of body mass for female, all are in 100% normal category.Keywords: Cardiorespiration Fitness, Mass Body Index.